Phenotypic detection of antimicrobial resistance mechanisms of Escherichia coli isolates from enteric infections in pigs from technified farms - Monterroso C., Michelle (2019)
The aim of this study was to detect the antimicrobial resistance mechanisms of 36 Escherichia coli isolates to beta-lactams, quinolones and aminoglycosides using the Kirby-Bauer technique. Thirty-six E. coli isolates from pigs of technified production farms obtained during the 2010-2015 period were used. Fifteen antimicrobials of importance in human and veterinary medicine were tested. The isolates showed resistance mainly to nalidixic acid (89%, 32/36), cloxacillin (83%, 30/36) and amoxicillin-clavulanic acid (69%, 25/36). Only 3% (1/36) were AmpC producers, 42% (15/36) showed a possible mutation in gyrA and 14% (5/36) at least two possible mutations in gyrA or gyrA+parC. In addition, 33% (12/36) showed high probabilities of presence of qnr genes. The enzymes associated to aminoglycoside resistance mechanism were positive in 39% (14/36) to AAC (6’), 28% (10/36) to ANT (2") and 11% (4/36) to AAC (3) IV.